Kaedah lelaran kumpulan tak tersirat dengan penghampiran beza terhingga peringkat tinggi bagi persamaan Poisson. - Jumat Sulaiman; Abdul Rahman Abdullah (Penerbit UTM Press, 1998)
In this paper, we extend the 2-Point Explicit Group Iterative (EGI) method the 3, 4, 6, 8 and 12-Point EGI methods with high-order difference approximation to solve the one dimiensional Poisson equation. We also describe the implementation of the EGI method with multigrid is compared without multigrid.